Phosphodiesterases : CNS functions and diseases. (Volume 17) - Zhang, Han-Ting. ; Xu, Ying. ; O'Donnell, James M. (Springer, 2020)
PDEs are a family of enzymes that catalyze the hydrolysis of intracellular cyclic neucleotides. They are implicated in a number of disorders and dysfunctions and PDE inhibitors have already proven to be effective therapies for erectile dysfunction, COPD, and psoriatic arthiritis. This family of enzymes also plays a role in diseases and disorders of the CNS such as depression, anxiety, schizophrenia, and Alzheimer's Disease. Unfortunately no effective PDE inhibitors have been developed for the treatment of these diseases. The proposed book will be a comprehensive overview of the current state of basic and translational research on PDE inhibitors written by internationally recognized experts. Authors will also discuss potential PDE subtypes and splice variants in the hopes that this will spur more creative approaches to PDE targeting drugs.Part I. PDEs and Signaling, Circuitry, and Implications of CNS Functions and Disorders -- 1. Phosphodiesterase Diversity and Signal Processing within cAMP Signaling Networks -- 2. Current Understanding of PDE10A in the Modulation of Basal Ganglia Circuitry -- 3. Interaction of Cdk5 and cAMP/PKA Signaling in the Mediation of Neuropsychiatric and Neurodegenerative Diseases -- 4. The PDE4 cAMP-specific Phosphodiesterases: Targets for Drugs with Antidepressant and Memory-enhancing Action -- 5. Phosphodiesterase-4B as a Therapeutic Target for Cognitive Impairment and Obesity-related Metabolic Diseases -- Part II. PDEs in Cognition of Aging and Alzheimer's Disease -- 6. From age-related Cognitive Decline to Alzheimer's Disease: A Translational Overview of the Potential role for Phosphodiesterases -- 7. The Past, Present, and Future of Phosphodiesterase-4 Modulation for age-induced Memory Loss -- 8. A Role for Phosphodiesterase 11A (PDE11A) in the Formation of Social Memories and the Stabilization of Mood -- 9. Role of PDE9 in Cognition -- Part III. PDEs in Parkinson's and Huntington's Diseases -- 10. Regulation of Striatal Neuron Activity by Cyclic Nucleotide Signaling and Phosphodiesterase Inhibition: Implications for the Treatment of Parkinson's Disease -- 11. Role of Phosphodiesterases in Huntington's Disease -- Part IV. PDEs and Psychiatric Disorders -- 12. The role of Phosphodiesterase-2 in Psychiatric and Neurodegenerative Disorders -- 13. Phosphodiesterase 1: A Unique Drug Target for Degenerative Diseases and Cognitive Dysfunction -- 14. PDE Inhibitors for the Treatment of Schizophrenia -- Part V. PDEs and Others -- 15. Targeting Phosphodiesterases in Pharmacotherapy for Substance Dependence -- 16. Genetic Understanding of Stroke Treatment: Potential role for Phosphodiesterase Inhibitors -- 17. A unique sub-pocket for Improvement of Selectivity of Phosphodiesterase Inhibitors in CNS.